Can Cold Plasma Be Used for Boosting Plant Growth and Plant Protection in Sustainable Plant Production? - Pańka, Dariusz; Jeske, Małgorzata; Łukanowski, Aleksander; Baturo-Cieśniewska, Anna; Prus, Piotr; Maitah, Mansoor; Maitah, Kamil; Malec, Karel; Rymarz, Dominika; Muhire, Jean de Dieu; Szwarc, Katarzyna (Agronomy (Basel), 2022)
Sustainable agriculture with low inputs of chemicals and fertilizers has been recently attracting more attention from producers and researchers in the EU. The main reason for such attention is The European Green Deal—the EU’s latest growth strategy concerning environmental degradation and climate change. One of its main components is the Farm to Fork strategy, which especially features the reduction in pesticide and mineral fertilizer application and also supports the development of organic farming. At the same time, food demand is rising. These ambitious challenges require extensive research, development and innovation. Therefore, new non-chemical techniques for improving plant growth and resistance to biotic and abiotic stresses must be explored for their potential in this field. One of the most promising is the use of non-thermal plasma for such purposes. As this physical factor is a complex mixture of ions, atoms, electrons, radicals and molecules, its effect on plants and pathogens is also complex. This review presents different aspects of the effect of non-thermal plasma on seed germination, development of seedlings, plants and pathogens. The literature was explored to provide evidence for the possible use of non-thermal plasma for boosting plant growth and plant protection.